2016
DOI: 10.1371/journal.ppat.1005918
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Abundance of Kaposi’s Sarcoma-Associated Herpesvirus ORF50 Protein by Oncoprotein MDM2

Abstract: The switch between latency and the lytic cycle of Kaposi’s sarcoma-associated herpesvirus (KSHV) is controlled by the expression of virally encoded ORF50 protein. Thus far, the regulatory mechanism underlying the protein stability of ORF50 is unknown. Our earlier studies have demonstrated that a protein abundance regulatory signal (PARS) at the ORF50 C-terminal region modulates its protein abundance. The PARS region consists of PARS-I (aa 490–535) and PARS-II (aa 590–650), and mutations in either component res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 41 publications
(72 reference statements)
4
29
0
Order By: Relevance
“…As shown in Figure 4 , FACS analysis of mCherry-positive cells revealed that treatment with Nutlin-3 alone induced a minor increase in lytic reactivation, which was enhanced when combined with Dox treatment. This result is in agreement with a previous report [ 45 ]. Combined treatment with Nutlin-3 and Dox together with induction of nucleolar stress with Act D or CX-5461 resulted in a further additive increase in the fraction of cells expressing mCherry.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As shown in Figure 4 , FACS analysis of mCherry-positive cells revealed that treatment with Nutlin-3 alone induced a minor increase in lytic reactivation, which was enhanced when combined with Dox treatment. This result is in agreement with a previous report [ 45 ]. Combined treatment with Nutlin-3 and Dox together with induction of nucleolar stress with Act D or CX-5461 resulted in a further additive increase in the fraction of cells expressing mCherry.…”
Section: Resultssupporting
confidence: 94%
“…Previous studies employing latently KSHV-infected cells have shown that inhibition of MDM2 by Nutlin-3, as well as genetic knockdown of MDM2 [ 45 ], result in activation of the tumor suppressor p53 pathway and stabilization of K-Rta leading to cell cycle arrest, massive cell death and disruption of viral latency. Based on these observations, we hypothesized that nucleolar stress, described as failures in ribosome biogenesis or function, which are often coupled with inhibition of MDM2 and p53 activation, might promote lytic reactivation of KSHV.…”
Section: Introductionmentioning
confidence: 99%
“…Coimmunoprecipitation analysis was performed as described previously ( 42 ). Briefly, 293T cells were cotransfected with expression vectors encoding myc-tagged NTPase and FLAG-tagged proteins as indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The target sequence of the c-Jun shRNA is 5′-ATTCGATCTCATTCAGTATTA. Preparation of shRNA lentiviral particles has been described previously [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…After washing with PBS to remove unbound virions, cells were cultured in normal or high glucose for another 24 hours. Immunofluorecent staining was performed as described previously [ 41 ]. For infecting B cells, BJAB cells were co-cultivated with 293T(BAC16) at a 3:1 ratio in normal or high glucose-containing media for 4 days.…”
Section: Methodsmentioning
confidence: 99%